Clinical efficacy and safety of astragalus injection combined with ACEI/ARB in the treatment of diabetic kidney disease: Protocol for a systematic review and meta-analysis. Issue 49 (9th December 2022) - Zhu, Zhiyue; Zhang, Qi; Liu, Le; Bao, Pengjie; Liu, Shilin; Song, Chaoqun; Yang, Wenbo; Nan, Zheng
Abstract : Background: Kidney disease is a common complication of diabetes and the main cause of end-stage renal disease. Astragalus (Huangqi) injection in combination with angiotensin-converting enzyme inhibitors/angiotensin receptor blockers (ACEI/ARBs) have been widely used for the treatment of diabetic kidney disease (DKD) in China. However, no supporting evidence yet exists with regard to the safety and effectiveness of this approach. Here a protocol is outlined for use in systematic evaluation of the safety and effectiveness of astragalus injection combined with ACEI/ARB for the treatment of DKD. Methods: Randomised controlled trials will be retrieved from 8 scientific databases, including PubMed, Web of Science, EMBASE database, Cochrane Library, China National Knowledge Infrastructure, Wanfang, China Biomedical Literature CD-ROM Database and China Science Journal Database. Ongoing clinical trial databases will also be searched for studies published from the time of establishment of each database to September 1, 2022. that will include the Chinese Clinical Trial Registration Centre (www.chictr.org.cn/ ), the World Health Organisation International Trial Registration Platform (https://www.who.int/clinical-trials-registry-platform ), Google Scholar (https://scholar.google.com/ ), Baidu Scholar (https://xueshu.baidu.com ), etc. The main outcome indicators included urinary albumin excretion rate or 24-hour urinary albumin excretion rate, and renal function (blood urea nitrogen, serum creatinine concentration). The secondary outcome indicators mainly include the following 4 aspects: blood sugar, blood pressure, blood lipid levels and adverse events. Two researchers will independently select and extract data from randomized controlled trials and determine risks of bias. Meta-analysis will be performed using Revman5.4 then the quality of evidence from randomized clinical trials will be assessed using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) System tool. Results: This review will be the first to summarize meta-analysis results regarding the efficacy and safety of Huangqi injection combined with ACEI/ARB when administered during any stage of diabetic nephropathy rather than during only a single stage of the disease. Discussion: It will provide high-quality guidance for the treatment of diabetic kidney disease and provide patients with more treatment options.